Liberal and Masonic Exile During the Reign of Ferdinand VII - Hinojal Aguado, Diego (2023)
Repression and exile defined the reign of Ferdinand vii. The French occupation of the Iberian Peninsula and the war and revolution that ensued as a result led to the spread of new political and social ideas that challenged absolute sovereignty. The monarch blamed Freemasonry for this and employed all means at his disposal to eradicate people and ideas that posed a threat to his crown, creating an atmosphere of fear and the risk of being outlawed. The arbitrary nature of these measures forced many individuals into exile to escape the constant threat of persecution.